2022
DOI: 10.3390/jcm11195547
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Door-To-Balloon Time between ST-Elevation Myocardial Infarction Electrocardiogram and Its Equivalents

Abstract: Background: In patients with ST-elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary interventions (pPCI), longer door-to-balloon (DTB) time is known to be associated with an unfavorable outcome. A percentage of patients with acute coronary occlusion present with atypical electrocardiographic (ECG) findings, known as STEMI-equivalents. We investigated whether DTB time for STEMI-equivalent patients was delayed. Methods: This is a retrospective study including patients arriving at an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
0
0
Order By: Relevance
“…Though findings showed a delay in PCI for about one-quarter of patients, shorter door-to-balloon intervals showed that the emergency response was quite good. It is pertinent to mention that for patients who need PCI, the door-to-balloon interval is considered a crucial time because the shorter door-to-balloon interval is associated with significantly reduced morbidity and mortality in ACS patients [ 47 , 48 ]. The results of the current study further showed that about 85% of the eligible patients were referred to cardiac rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Though findings showed a delay in PCI for about one-quarter of patients, shorter door-to-balloon intervals showed that the emergency response was quite good. It is pertinent to mention that for patients who need PCI, the door-to-balloon interval is considered a crucial time because the shorter door-to-balloon interval is associated with significantly reduced morbidity and mortality in ACS patients [ 47 , 48 ]. The results of the current study further showed that about 85% of the eligible patients were referred to cardiac rehabilitation.…”
Section: Discussionmentioning
confidence: 99%